PERUBAHAN PERATURAN MENTERI AGAMA (PMA) NOMOR 19 TAHUN 2018 TENTANG KETENTUAN WALI NASAB DALAM PERSPEKTIF HUKUM ISLAM - Janah, Latifah Nur (Fakultas Syariah, Universitas Islam Negeri Raden Mas Said Surakarta, 2020)
Abstract Amendments To The Regulation Of The Minister Of Religion (PMA) Number 19 Of 2018 Concerning With Provisoin Of The Customers Of Islamic Legal Perspectives. This article discusses the changes in the Minister of Religion's Regulation (PMA) regarding the conditions of a nasab guardian's conditions in marriage, which eliminates the minimum age requirement for age and independence. The terms of independence are considered to be incompatible with the times. As for the changes that occurred regarding balig reviewed using the opinion of Islamic scholars, the opinions of experts in psychology, as well as positive law in Indonesia. According to Imam Hanafi, the age of age is 18 for men, while 17 for women. According to Imam Shafi'i the age limit for men is 15 years while for women 9 years. Imam Hambali provides a limit of 15 years for men and hayá¸ for women. Meanwhile, according to Imam Malik, namely the growth of hair in several members of the body. According to experts balig began at the age of 14-17 years in the puberty period and 17-21 years in the adolensation period. According to Law Number 1 of 1974, it is legal for men, 19 years and 16 years for women. Whereas the Compilation of Islamic Law is 16 years old. The difference from the following opinions makes there is no definite measure of when someone has been old. This type of research is a qualitative literary study with data analysis techniques, descriptive analytic. Keywords: Nasab Guardian; Islamic Law; Baligh. Abstrak Perubahan Peraturan Menteri Agama (PMA) Nomor 19 TahunÂ 2018 Tentang Ketentuan Wali Nasab Dalam Perspektif Hukum Islam. Artikel ini membahas mengenai perubahan yang ada pada Peraturan Menteri Agama (PMA) perihal ketentuan syarat seorang wali nasab dalam pernikahan, dimana menghapuskan syarat minimal usia balig dan merdeka. Syarat merdeka dianggap telah tidak sesuai dengan perkembangan zaman. Adapun perubahan yang terjadi mengenai balig diulas menggunakan pendapat ulama madzhab, pendapat dari para pakar psikologi, serta hukum positif Indonesia. Menurut Imam Hanafi balig bagi laki-laki yaitu 18 tahun sedangkan 17 tahun bagi perempuan. Menurut Imam Syafi'i batasan balig bagi laki-laki adalah 15 tahun sedangkan perempuan 9 tahun. Imam Hambali memberikan batasan 15 tahun bagi laki-laki dan hayá¸ bagi perempuan. Sedangkan menurut Imam Malik yaitu tumbuhnya rambut dibeberapa anggota tubuh. Menurut para pakar balig dimulai pada umur 14-17 tahun pada periode pubertas dan 17-21 tahun pada periode adolensesi. Menurut Undang-Undang Nomor 1 Tahun 1974 balig untuk laki-laki yaitu 19 tahun dan 16 tahun bagi perempuan. Sedangkan Kompilasi Hukum Islam berumur 16 tahun. Perbedaan dari pendapat-pendapat berikut membuat tidak ada ukuran pasti kapan seseorang telah balig. Jenis penelitian ini adalah penelitian kualitatif literer dengan teknik analisis data, deskriptif analitik. Kata Kunci: Wali nasab; Hukum Islam; Baligh.